Mathematical modeling of Bacillus cereus in Saengsik, a powdered ready‐to‐eat food and its application in quantitative microbial risk assessment. Issue 1 (11th November 2022) - Hwang, Daekeun; Park, Jin Hwa; Yoon, Yohan; Ha, Sang‐Do; Rhee, Min Suk; Koo, Minseon; Kim, Hyun Jung
Abstract: In this study, we developed a mathematical model to describe the fate of Bacillus cereus in Saengsik, a powdered ready‐to‐eat food with reduced moisture content, and to estimate the probability of B. cereus infection from Saengsik consumption, using quantitative microbial risk assessment (QMRA). The isothermal kinetic behavior of B. cereus was analyzed as a function of temperature (5–40°C). Bacterial cell counts were fitted to the Weibull model using GinaFit, and the obtained delta values (required time for the first decimal reduction) for each temperature were 128.3–17, 124.1 hr and concave ( ρ < 1) were observed under all experimental conditions. The obtained delta values were analyzed using the Davey model as a function of temperature, and the performance of the developed model of survival of B. cereus was appropriate based on the validation parameters ( B f, A f, and RMSE) within the acceptable range. QMRA model was developed using data on the prevalence and concentration of B. cereus along with time and temperature along the retail‐to‐consumer steps. Using a baseline model with the currently available data, the probability of B. cereus infection was zero. These results provide useful information for the risk assessment and management of microbial risk in foods, especially those with very low‐moisture content. Abstract : In this study, we developed a mathematical model to describe the fate of Bacillus cereus in Saengsik, a powdered ready‐to‐eat food with reduced moisture content, and to estimate the probability of B. cereus infection from Saengsik consumption, using quantitative microbial risk assessment (QMRA).